Work like a Doc: A comparison of regulations on residents' working hours in 14 high-income countries - Maoz Breuer, Rina; Waitzberg, Ruth; Breuer, Adin; Cram, Peter; Bryndova, Lucie; Williams, Gemma A; Kasekamp, Kaija; Keskimaki, Ilmo; Tynkkynen, Liina-Kaisa; van Ginneken, Verena; Kovács, Eszter; Burke, Sara; et al. (Health policy (Amsterdam, Netherlands), 2023)
BACKGROUND: Medical residents work long, continuous hours. Working in conditions of extreme fatigue has adverse effects on the quality and safety of care, and on residents' quality of life. Many countries have attempted to regulate residents' work hours. OBJECTIVES: We aimed to review residents' work hours regulations in different countries with an emphasis on night shifts. METHODS: Standardized qualitative data on residents' working hours were collected with the assistance of experts from 14 high-income countries through a questionnaire. An international comparative analysis was performed. RESULTS: All countries reviewed limit the weekly working hours; North-American countries limit to 60-80 h, European countries limit to 48 h. In most countries, residents work 24 or 26 consecutive hours, but the number of long overnight shifts varies, ranging from two to ten. Many European countries face difficulties in complying with the weekly hour limit and allow opt-out contracts to exceed it. CONCLUSIONS: In the countries analyzed, residents still work long hours. Attempts to limit the shift length or the weekly working hours resulted in modest improvements in residents' quality of life with mixed effects on quality of care and residents' education.
Keywords: Workload; Medical residents; Work hours; personální obsazení a rozvrh; kurzy a stáže v nemocnici; Cross-country analysis; Humans; Internship and Residency; pracovní zátěž; ACGME; Quality of Life; vyspělé země; Nightshifts; EWTD; kvalita života; Developed Countries; Personnel Staffing and Scheduling; lidé